Oxidative stress, DNA damage and apoptosis induced by tebuconazole in the kidney of male Wistar rat. (1st October 2020) - Othmène, Yosra Ben; Hamdi, Hiba; Salem, Intidhar Ben; Annabi, Emna; Amara, Ines; Neffati, Fadwa; Najjar, Mohamed Fadhel; Abid-Essefi, Salwa
Abstract: Tebuconazole (TEB) is a broad-spectrum conazole fungicide that has been used in agriculture in the control of foliar and soil-borne diseases of many crops. The present study has investigated the adverse effects of subchronic exposure to TEB on the kidney of male rats. Animals were divided into four equal groups and treated with TEB at increasing doses 0.9, 9 and 27 mg/kg body weight for 28 consecutive days. The results showed that TEB induced oxidative stress in the kidney demonstrated by an increase in malondialdehyde (MDA), protein carbonyl (PC), advanced oxidation protein product (AOPP) levels and DNA damage, as compared to the controls. Furthermore, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) activities were increased in the renal tissue of treated rats. Moreover, significant decrease in reduced glutathione (GSH) content in TEB-treated rats was observed, while oxidized glutathione (GSSG) levels were increased, thus a marked fall in GSH/GSSG ratio was registered in the kidney. Glutathione reductase (GR) activity showed a significant increase after TEB exposure. Moreover, TEB down-regulated the expression of Bcl2 and up-regulated the expression of Bax and caspase 3, which triggered apoptosis via the Bax/Bcl2 and caspase pathway. Also, TEB administration resulted in altered biochemical indicators of renal function and varying lesions in the overall histo-architecture of renal tissues. Taken together, our findings brought into light the renal toxicity induced by TEB, which was found to be significant at low doses. Graphical abstract: Image 1 Highlights: TEB exposure induced oxidative stress in the kidney. TEB exposure increased MDA, PC and AOPP levels. TEB-treated rats showed modified endogenous antioxidants activity. TEB exposure was associated with biochemical and histopathological changes. TEB exposure induced DNA damage and apoptosis induction.